Complete nucleotide sequence of the influenza A/PR/8/34 virus NS gene and comparison with the NS genes of the A/Udorn/72 and A/FPV/Rostock/34 strains. - Baez, M (1980)
The nucleotide sequence of the NS gene of the human influenza virus A/PR/8/34 was determined and found to be the same length (890 nucleotides) as the NS gene of another human influenza virus A/Udorn/72 and of the avian isolate A/FPV/Rostock/34. Comparison of the sequences of the NS genes of the two human influenza viruses shows an 8.9% difference whereas the NS gene of the avian isolate differs by only 8% from that of the human strain A/PR/8/34. The extensive sequence similarity among these three genes does not support the notion of species specific homology groups among NS genes of avian and human influenza virus strains. The primary sequence of the A/PR/8/34 NS gene is consistent with the findings that the influenza virus NS gene may code for two overlapping polypeptides. In addition, an open reading frame potentially coding for a polypeptide 167 amino acids in length was found in the negative strand RNA of the A/PR/8/34 virus NS gene.